3D-printed monolithic porous adsorbents from a solution-processible, hypercrosslinkable, functionalizable polymer - Lee, Junghyun (2022)
Solid adsorbents have been actively developed for energy-efficient gas separations including carbon capture and air purification. However, conventional particulate adsorbents often show ineffective mass transfer and significant pressure drop in practical operations, leading to a limited overall performance. As a potential solution to these issues, the development of three-dimensionally (3D) structured adsorbents has been proposed. Herein, we report a novel approach to design 3D monolithic adsorbents for CO2 separation via 3D printing of a processible polymer, which in turn can be transformed into a functional porous material via hypercrosslinking and amine-grafting. Importantly, such structure can be realized without an aid from binders or mechanical supports. Our adsorbents demonstrated a promising CO2 adsorption performance without experiencing any pressure drop under dynamic flow condition. The stability and regenerability, which are also important requirements for practical operations, were also successfully demonstrated through a repetitive adsorption–desorption cycling test in the presence of water vapor. We envisage that our approach can be applied in the development of structurally versatile adsorbents for various gas separation processes.